Peran Grit pada Mahasiswa Penerima Beasiswa Prestasi yang Aktif Berorganisasi - Widya Annisa Royani; Cindy Julistya Siswanto; Vio Angelina Ongkowiyono; Naomi Aryandini Subagio; Feilicya Aurellia Wijaya; Aldona Annisa Rohma (Universitas Ciputra Surabaya, 2024)
The academic demands of scholarship students in maintaining GPA as well as being active in organizations, requires students to persevere in their efforts to achieve long-term goals, even though they are faced with various challenges. This study aims to explore the aspects that form grit and the role of grit in scholarship recipients who are active in student organizations. The researchers use a qualitative method with an instrumental case study. The sampling technique used is purposive sampling. Data collection was carried out through semi-structured interviews and documents as supporting data. Data analysis using thematic analysis. The result of the study showed that there are three aspects that form grit, namely perseverance of effort, consistency of interest and adaptability. Then, the role of grit in facing challenges was also discovered, which is problem solving and never giving up. Another interesting finding is the supporting factors of grit, which is belief in God and received social support. It can be concluded that grit plays an important role in helping students face challenges for achieving their long-term goals.